Твердотельные СВЧ-модули для радиотехнической аппаратуры и систем миллиметрового диапазона длин волн - Karushkin, N. F.; Maltsev, S. B.; Khitrovskiy, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2016)
The paper presents scientific, technological and production potential of Research Institute «Orion» in the field of creation of wide range of high performance active and passive solid-state microwave devices, modules and components as well as multifunctional devices on their basis. These products taken as a whole form a component base for promising equipment and systems working in the frequency range from 1.0 to 200 GHz.